2012
DOI: 10.1007/s00240-012-0468-0
|View full text |Cite
|
Sign up to set email alerts
|

Topical EMLA for pain control during extracorporeal shock wave lithotripsy: prospective, comparative, randomized, double-blind study

Abstract: Patient collaboration in external shock wave lithotripsy (ESWL) is critical for its correct application, making proper analgesic selection indispensable. The aim of this study was to evaluate the efficacy of combined application of EMLA and intravenous (i.v.) pethidine compared with pethidine plus placebo cream in patients undergoing ESWL for ureteral and/or renal lithiasis. Prospective, controlled, randomized, double-blind study was conducted in patients receiving ESWL for renal and/or ureterolithiasis. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 20 publications
0
13
0
1
Order By: Relevance
“…A sensitivity analysis was performed to evaluate the stability of the results due to a significant heterogeneity in the primary outcome among studies. After removing one study at a time, we found that the heterogeneity was mainly caused by Vilar et al [17]. After removing this study, the pain reduction effect by EMLA became insignificant (RR = -1.30, 95% CI = -3.25 to -0.65, P = 0.19) with a low heterogeneity of I 2 = 4% (P = 0.38, Fig 3).…”
Section: Pain Controlmentioning
confidence: 87%
See 3 more Smart Citations
“…A sensitivity analysis was performed to evaluate the stability of the results due to a significant heterogeneity in the primary outcome among studies. After removing one study at a time, we found that the heterogeneity was mainly caused by Vilar et al [17]. After removing this study, the pain reduction effect by EMLA became insignificant (RR = -1.30, 95% CI = -3.25 to -0.65, P = 0.19) with a low heterogeneity of I 2 = 4% (P = 0.38, Fig 3).…”
Section: Pain Controlmentioning
confidence: 87%
“…An additional explanation could be that a cream-skin interface has less absorption and reflection of energy, leading to less skin trauma and pain. On the other hand, this interface also brings more energy transmission to the stones, which results in a lower numbers of required shock waves and total energy as demonstrated by Vilar et al [17,24]. Accordingly, the authors found better stone fragmentation in the EMLA-treated group.…”
Section: Plos Onementioning
confidence: 87%
See 2 more Smart Citations
“…Vilar, et al, in their analysis, used intravenous pethidine and EMLA cream in one group and intravenous pethidine and placebo cream in another group for pain control during ESWL. They concluded that EMLA cream combined with intravenous pethidine improved the visual analogue score, stone fragmentation, and decreased rate of withdrawal from ESWL procedure versus intravenous pethidine and placebo cream [15]. Similarly, Kumar, et al showed improved pain control and better stone-free rate with topical EMLA cream in combination with diclofenac sodium as compared to either of the entities used alone [16].…”
Section: Discussionmentioning
confidence: 99%